A systematic review protocol of educational programs for nursing staff on management of resident‐to‐resident elder mistreatment in residential aged care homes. (31st May 2018) - Ellis, Julie M.; Ayala Quintanilla, Beatriz Paulina; Ward, Louise; Campbell, Fergus; Hillel, Stav; Downing, Carolyn; Teresi, Jeanne; Ramirez, Mildred
Abstract: Aim: To review evidence concerning educational programs for nursing staff on management of resident‐to‐resident elder mistreatment with the aim of preventing and reducing this abuse in residential aged care homes. Background: Although elder abuse has received considerable attention, very little is known regarding resident‐to‐resident elder mistreatment in residential aged care homes and about interventions/programs to prevent and reduce this harm. Nurses play an essential role in identifying and managing aggressive interactions. However, many nurses may not recognize these behaviours as forms of abuse. Thus, it is important to ascertain if educational programs for nursing staff have been developed and implemented. Design: Quantitative systematic review registered on PROSPERO (CRD42017080925). Methods: A systematic search of English published studies between 1980 ‐ 2017 will be conducted in CINAHL, Embase, MEDLINE, ProQuest, PsychInfo and Scopus. Risk of bias and quality of the studies will be evaluated by using the Cochrane Collaboration′s tool and the Methodological Index for Nonrandomized studies. A meta‐analysis will be performed, if sufficient homogeneity exists; otherwise, data will be summarized by using a narrative description. This study was funded in January 2017. Discussion: Nursing staff should play a pivotal role in preventing and/or reducing resident‐to‐resident elder mistreatment. Therefore, it is important to identify available educational programs for nursing staff dealing with this abuse. Consequently, this review may provide evidence‐based care for nursing staff to assist them in protecting older residents from experiencing abuse or being abused and in improving their well‐being.